Impurity effects on quasi-linear heat transport induced by interaction of TEM and ITG turbulence. (22nd October 2021) - Li, J.; Wang, Z.X.; Dong, J.Q.; Shen, Y.; Zou, X.L.; Zhong, W.L.; Du, H.R.; Wang, L.F.; Han, M.K.; Zhang, X.R.; Liu, J.Y.; Xiao, G.L.; et al.
Abstract: The impurity effects on quasi-linear turbulent heat transport induced by ion temperature gradient and trapped electron modes in tokamak plasmas are numerically studied, using a full gyrokinetic description for main and impurity ions. The unstable modes in independent and hybrid states are all taken into account. The fluxes integrated over the complete spectrum rather than taking an individual characteristic k θ ρ s of poloidal wave-vector are systematically investigated. The results indicate that the injected impurity enhances the heat transport of main ions and electrons, and the maximum variations of the former are shown to be approximately twice as high as those of the latter, i.e. Δ Q i−sum ∼ 2Δ Q e−sum for the core plasmas of the parameters in this work. In contrast, the impurity ions can induce reduction of the edge ion heat fluxes, while the electron heat fluxes are almost unchanged. Such distinct behaviors are found to be associated with the transition of instabilities types and dominated regimes of heat transport. Significantly, reversed magnetic shear, large temperature ratios of electrons to main ions as well as high mass numbers of impurity ions contribute to the improvement of confinement and formation of energy pinch. The newly updated code identifies individual contributions to heat transport from conductive and convective fluxes, both of which are composed of diagonal, off-diagonal diffusive and non-diffusive components and thus is expected to be a powerful tool for experimental data analysis as well. The phase shift (larger than π /2) is demonstrated to be a reasonable mechanism for the induction of energy pinch.